Orthotic Device Use in Canine Patients: Owner Perception of Quality of Life for Owners and Patients - Lee, Sera; Wendland, Theresa M.; Rao, Sangeeta; Magee, Christianne (Frontiers in Veterinary Science, 2021)
Orthotic devices are an established treatment for neuromusculoskeletal disease in the human population. Orthoses are an emerging veterinary therapy due to limited practitioner experience, availability of devices, and published data from veterinary patient outcomes. Expanding client education and veterinary expertise in the application of orthoses may allow greater access and successful utilization of these devices to treat appendicular disease. While orthoses have the potential to improve quality of life for veterinary patients, consideration needs to be made for owner related factors with device use. Owner satisfaction and experience may greatly impact compliance with treatment recommendations; therefore, it is crucial that owner expectations are met. The purpose of the present study was to evaluate owner-reported outcomes of orthosis for canine patients and their owner's subjective responses about the shared pet/owner experience utilizing a promoter score. It was hypothesized that owner's impressions of their pet's experience with the orthotic device would influence owner perceptions of quality of life for both the owner and the pet, and these factors would impact the likelihood of the owner to recommend a veterinary orthosis to a friend. An anonymous online survey was sent to 136 clients of a single veterinary orthoses manufacturer. Fifty-six surveys were completed and included for analysis. The owner's reported quality of life was in agreement (P = 0.02) with reported pet quality of life. There was also a higher likelihood (P = 0.02) for the owner to recommend a veterinary orthotic device to a friend when owner perceptions of pet quality of life were positive as compared to negative or neutral. Willingness to recommend an experience to a friend is a reflection of satisfaction with the experience. The dependence of owner and pet quality of life should therefore guide therapeutic decisions for patient management and client communication to ensure that the orthosis experience is positive for both patient and owner.